Investigating the Enhancement of Solubility of Poorly Water-Soluble Drugs Diclofenac Sodium by Mixed Solvency Approach - Masheer Ahmed Khan (Challenges and Advances in Chemical Science Vol. 6, 2021)
One of the difficult tasks that becomes a challenge in the formulation development of an orally administered drug with poor aqueous solubility is increasing solubility. Drugs with low water solubility have a hard time producing formulations with enough bioavailability, preventing them from being used effectively. The ’mixed-solvency’ notion refers to the phenomena of increasing the solubility of poorly water-soluble pharmaceuticals in an aqueous solution containing blends of hydrotropic agents, co-solvents, and water-soluble solutes that may have a synergistic influence on drug solubility. In this study, a mixed solvency approach was used to improve the aqueous solubility of the poorly water-soluble drug diclofenec sodium (selected as a model drug) by blending a variety of water-soluble substances from the hydrotropic (urea, sodium acetate); water soluble solutes (PEG4000, PEG6000); and co-solvents (PEG200, PEG400). At room temperature, the aqueous solubility of diclofenac sodium was observed in randomly selected blends of solubilizers containing different combinations while maintaining a total concentration of 50% w/v constant. In the concentration range of 10-60 \(μ\)g/ml., diclofenec sodium has a \(λ\)max of 276 nm and follows Beers Law. The findings suggest that using a mixed solvency approach, the solubility of diclofenac sodium containing blends of various combinations was significantly improved.